The Breeding Distribution and Current Population Status of the Ivory Gull in Canada - Thomas, V.G.; MacDonald, S.D. (ARCTIC, 1987)
Aerial surveys were conducted in the eastern Canadian High Arctic from 1982 to 1985 to determine the distribution and size of breeding populations of the ivory gull (Pagophila eburnea). The known Canadian population is confined to Ellesmere, Devon, Seymour, Baffin and Perley islands. Two major concentrations of ivory gull colonies exist, one among the granitic nunataks of southeastern Ellesmere Island and the other on the sedimentary plateaus of the Brodeur Peninsula of Baffin Island. The size of breeding groups varies greatly from 4 to over 300 adult gulls. Breeding colonies are typified by their inland, remote and desolate locations and virtual absence of other animal species. We suggest that there is a single Canadian population of ivory gulls whose adult cohort contains over 2400 birds. The small number of leg band recoveries and retrapping of banded birds indicates that individuals can live at least 15 years. One-year-old ivory gulls were not seen at the colonies or on adjacent waters, and their location during summer remains unknown.Key words: ivory gull, Pagophila eburnea, arctic breeding populations, nunataks, polynyas On a effectué des relevés aériens dans la partie est de l'Extrême-Arctique canadien de 1982 à 1985 pour établir la distribution et la taille des populations de mouettes blanches (Pagophila eburnea) qui se reproduisent. La population canadienne que l'on connaît habite seulement les îles Ellesmere, Devon, Seymour, Baffin et Perley. Il y a deux endroits importants où se concentrent les colonies de mouettes blanches, l'une parmi les nunataks granitiques du sud-est de l'île Ellesmere, et l'autre sur les plateaux sédimentaires de la presqu'île Brodeur dans l'île Baffin. La taille des groupes qui se reproduisent varie grandement, allant de 4 à plus de 300 oiseaux adultes. Les colonies d'animaux qui se reproduisent sont caractérisées par leur aire de nidification isolée, loin à l'intérieur des terres, et par l'absence virtuelle d'autres espèces animales. Notre opinion est qu'il existe une seule ...